The contributions of didactic projects to the teaching of Natural Sciences in rural schools - Raimunda Alves Melo Alves Melo; Antonia Dalva França-Carvalho; Weslley Alves (Universidade Federal do Norte do Tocantins, 2023)
The general objective of this study was to analyze the contributions of didactic projects to the teaching of Natural Sciences in rural schools, evidencing relations with the theoretical-methodological principles of Rural Education. To this end, the characterization of the pedagogical practice of the teachers researched was carried out, highlighting the contributions of the projects to the overcoming of traditional pedagogical practices. Field research with a qualitative approach was carried out, and the questionnaire and document analysis of the didactic projects developed in the researched school were used as data production devices. The research field was the Manoel Francisco School Unit, located in the rural community of Baixinha, located about 40 km from the seat of the municipality of Sigefredo Pacheco - Piauí. The interlocutors were two teachers of Natural Sciences who work in the final years of Elementary School. The results indicate that the didactic projects contribute to the teaching of Natural Sciences in rural schools respecting some theoretical-methodological principles of Rural Education, among which the following stand out: the valorization of the students' experiences; the problematization and study of reality; the proposition of interventions; horizontality in the teacher-student relationship, favoring meaningful teaching focused on the students' desires and needs.